Proactivity towards workplace safety improvement: an investigation of its motivational drivers and organizational outcomes. Issue 2 (4th March 2019) - Curcuruto, Matteo; Parker, Sharon K.; Griffin, Mark A.
ABSTRACT: Initiating a safety oriented change—or safety initiative —is conceptually distinct from other forms of safety participation and safety citizenship behaviour, yet little attention has been given to its performance outcomes or its motivational antecedents. An initial study with a sample composed of middle managers ( N = 86) showed that safety initiative predicted objective improvement actions 6 months later, whereas, showing differential validity, safety compliance predicted the implementation of monitoring actions. Two subsequent studies focused on motivational antecedents. First, using a sample of team leaders ( N = 295), we tested a higher-order structure of proactive motivation that incorporates three domains: "can do", "reason to" and future orientation. Second, in a longitudinal study of chemical work operators ( N = 188), after checking for the influence of potential confounders (past behaviours; accidents experience; perceived risk), we showed that safety initiative was predicted only by proactive motivation. Instead, safety compliance was found to be associated with affective commitment and scrupulousness, whereas safety helping was found to be associated with affective commitment. Self-reported behaviours were validated against rater assessments. This study supports the importance of distinguishing safety initiative from other safety behaviours, indicating how to create an organizational context supporting a proactive management of workplace safety.